Utilization of Instagram as a Medium for Advertising and Promotion of MSMEs in The Food Sector of Kembangringgit Village - Mochammad Rigel Putra; Poppy Febriana; Khuzaima Dwi Nur'aini (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In today's digital era, some business people use social media to increase their selling power and relationships with consumers. Social media provides new things in doing business and communicating using communication techniques between business actors and customers. Making it one of the advantages in the field of product marketing promotion. One of the social media choices is Instagram, which is used by business people to promote their products or reach a wider sales market. The purpose of this study was to describe the use of social media Instagram as a promotional medium for MSMEs in Kembangringgit Village.